The impact of artificial sweeteners on the risk and course of large intestinal adenocarcinoma in the elderly - Martyna Anna Goljat; Paweł Niewiadomski; Maciej Lazarek; Ewelina Flegiel; Karolina Graczykowska; Michał Denkiewicz; Ewa Rozmarynowicz; Magdalena Walczak; Marta Cybulska; Jakub Husejko; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
There are many confirmed risk factors for development of the colorectal cancer, which is one of the most common malignant tumor among both females and males. Moreover, it is a cause of significant percentage of all cancer-related deaths. Even with treatment, the 5-year survival rate is very low. We concentrate on impact of artificial sweeteners on risk and course of adenocarcinoma of colon.